Na+ channel function, regulation, structure, trafficking and sequestration. (13th March 2015) - Chen‐Izu, Ye; Shaw, Robin M.; Pitt, Geoffrey S.; Yarov‐Yarovoy, Vladimir; Sack, Jon T.; Abriel, Hugues; Aldrich, Richard W.; Belardinelli, Luiz; Cannell, Mark B.; Catterall, William A.; Chazin, Walter J.; Chiamvimonvat, Nipavan; et al.
Abstract : Abstract: This paper is the second of a series of three reviews published in this issue resulting from the University of California Davis Cardiovascular Symposium 2014: Systems approach to understanding cardiac excitation–contraction coupling and arrhythmias: Na + channel and Na + transport . The goal of the symposium was to bring together experts in the field to discuss points of consensus and controversy on the topic of sodium in the heart. The present review focuses on Na + channel function and regulation, Na + channel structure and function, and Na + channel trafficking, sequestration and complexing.